Incidence of infections in patients with pemphigus vulgaris - Narain, Upma; Kant, Tejas; Kant, Arun (International Journal of Advances in Medicine, 2022)
Background: Pemphigus is a rare, chronic autoimmune blistering disease of skin and mucous membranes. Autoimmune process and immunosuppressive therapy of pemphigus vulgaris would predispose the patients to infections. Therefore, the objective of this study was to isolate and identify the pathogens in admitted patients suffering from pemphigus vulgaris. Methods: This was a retrospective observational study based on 68 diagnosed cases of pemphigus vulgaris (PV) admitted during January 1999 to April 2018 in SRN hospital, MLN medical college Prayagraj. Patients who had PV and required admission owing to development of severe symptoms were included while patients with mild symptoms were excluded from the study. These admitted patients, along with routine and radiological examination, were also examined for microbiological examinations of sputum, throat swab, blood, body fluids, skin scrapings, stool and urine when necessary. Results: Out of the 68 patients, 66.17% patients developed bacterial infections while 33.83% developed fungal infections. The prevalence of bacterial and fungal pathogens in urinary tract is 72.42% and 27.58%, pneumonitis is 29.42% and 70.58%, septicaemia is 81.82% and 18.18% and skin and soft tissue is 87.50% and 12.50% respectively. In meningitis and pulmonary tuberculosis no traces of fungi were recorded. Mortality was seen in 7.35% patients, which was due to bacterial meningitis, septicaemia and fungal pneumonitis. Conclusions: The present study clearly states that the occurrence of the disease is uncommon but secondary infections are associated with worse prognosis. Therefore, the best regimen for each type of patients should base on the extent of disease and patient’s comorbidities.